1993
DOI: 10.1083/jcb.121.4.923
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant entactin promotes mouse primary trophoblast cell adhesion and migration through the Arg-Gly-Asp (RGD) recognition sequence [published erratum appears in J Cell Biol 1993 Jul;122(1):279]

Abstract: Abstract. In vitro culture of mouse blastocysts during the period coinciding with implantation has revealed that primary trophoblast cells can adhere and migrate in serum-free medium when provided with certain extracellular matrix components, including fibronectin and laminin. Tightly associated with laminin is the glycoprotein, entactin, that may play an important role in basement membrane assembly and cell attachment. Mouse blastocysts were studied using this in vitro model to determine whether entactin was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
60
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(60 citation statements)
references
References 43 publications
0
60
0
Order By: Relevance
“…A minor inhibition of NKp30-induced IL-2 production could be detected only at the highest rNID1 concentration. Since NID1 has been reported to interact with α3β1 (CD49a/CD29) and αvβ3 (CD51/CD61) integrins, 53,54 we analyzed the expression of CD29, CD49a, and CD61 in Bw-NKp44 and Bw-NKp30 cells, to rule out possible biases in the functional data on NID1. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A minor inhibition of NKp30-induced IL-2 production could be detected only at the highest rNID1 concentration. Since NID1 has been reported to interact with α3β1 (CD49a/CD29) and αvβ3 (CD51/CD61) integrins, 53,54 we analyzed the expression of CD29, CD49a, and CD61 in Bw-NKp44 and Bw-NKp30 cells, to rule out possible biases in the functional data on NID1. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In this context, it has been reported that NID1 may associate through the interaction of its RGD sequence with α3β1 or αvβ3 integrins. 53,54 Notably, we could detect surface NID1 on a panel of different NKp44Fc-binding human tumor cell lines (Figure 11). Although it has been reported that NID1 up-regulation occurs in several tumor types, information is still lacking on whether NID1 is associated to the tumor cell surface.…”
Section: Discussionmentioning
confidence: 98%
“…However, OPN null females do not show any reproductive defects and, therefore, other integrin activators must induce blastocyst activation corporately with OPN. In fact, both fibronectin and entactin, RGD motif-containing proteins, promote mouse blastocyst adhesion [26,27]. Although OPN is recently reported to be one of mediators in embryo-uterine interactions, HB-EGF is the one which was initially identified and is the most wellknown [1], and is fully described in the section ''Heparinbinding epidermal growth factor-like growth factor''.…”
Section: Osteopontinmentioning
confidence: 99%
“…The invasive trophoblasts of mouse blastocysts adhere, spread, and migrate on extracellular matrix (ECM) substrates [36][37][38][39] and penetrate the three-dimensional ECM structures [40]. The TE of the implantation-induced blastocyst alters its functional programming via changes in cell surface molecules.…”
Section: Extracellular Proteins and Tinagl1 In The Basement Membrane mentioning
confidence: 99%